Post-conflict monetary reconstruction - Adam, C; Collier, P; Davies, V (Oxford University Press, 2008)
During civil war governments typically resort to inflation to raise revenue. In this paper we model and quantify this phenomenon and then apply it to the choices and constraints faced in the post-conflict period. We show that far from there being a fiscal peace dividend, post-conflict governments tend to face even more pressing needs than during war. In consequence, in the absence of post-conflict aid, inflation sharply increases, frustrating a more general monetary recovery. Aid decisively transforms the path of monetary variables in the post-conflict period, enabling the economy to regain peacetime characteristics. Post-conflict aid thus accomplishes a monetary ‘reconstruction’ analogous to its more evident role in infrastructure.